Inclusive growth and the sophisticated influence of carbon emissions, renewable energy, and financial development: An introspective analysis of Africa - Nketia, E.B.; Kong, Y.; Mensah, I.A.; Ampon-Wireko, S.; Anfom, K. (Taylor and Francis Ltd., 2022)
This study investigates how inclusive growth is affected by carbon emission, renewable energy, and the new financial development index using 48 African countries categorized into low-income countries (LIC) and middle-income countries (MIC) spanning from 2000 to 2018. Bearing in mind the presence of residual cross-sectional reliance and heterogeneity in a panel data settings, the study employed robust estimations econometric approaches which includes the Augmented Mean group (AMG), Driscoll-Kraay (DK) standard errors method together with the Correlated Effects Mean Group (CCEMG) technique. The study’s outcomes from the mentioned approaches showed that; carbon emission positively affects inclusive growth in aggregate African panel, and LIC but not in MIC panels correspondingly. Furthermore, renewable energy significantly mitigates inclusive growth in LIC group African nations, but not significant in Africa as a whole or in MIC country grouping. Financial development is homogeneously positive and significant, with inclusive growth across all panels of African economies. The outlined outcomes were also confirmed by the Generalized Method of Moments (System-GMM). Based on the outlined study preferably suggest that carbon emission in LIC must be focused on attracting investments with low carbon footprints. On renewable energy, it is further recommended that both LIC and MIC should sticks to the African Renewable Energy Initiative.
Research Article
Keywords: Africa; Carbon emission; Financial development; Inclusive growth; Renewable energy